Systematic review of the literature on instruction for the implementation of discrete trial training (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Discrete-trial training (DTT) has proven to be effective to teach a variety of skills to individuals diagnosed with autism spectrum disorder. The purpose of the present study was to analyze the recent literature about teaching DTT to professionals and parents. We conducted searches in PsycINFO and ERIC databases with the terms “discrete trial training”, “discrete trials”, “DTT”, “discrete trial”, “discrete trial instruction” combined with “developmental disabilities”, “autism” and “training” from 2018 to 2023. Fifteen studies met inclusion criteria. Behavioral skills training (BST) was the most commonly implemented training procedure and telehealth has been used to minimize the presence of the trainer during training. Besides BST, other procedures were effective to teach the implementation of DTT. Future studies should compare those different teaching procedures and identify the variables involved in the advantages and in the disadvantages of each procedure.
Keywords: Applied Behavior Analysis; autism spectrum disorder; discrete trial training; training